Our environment. - Kinney, Karin (Alexandria, Virginia : Time-Life Books, 1999)
Describe's the world's diverse habitats and the close relationships between plants and animals, including humans, who must share those habitats.
Includes index.
NLP
Keywords: Habitat (Ecology) -- Juvenile literature; Nature conservation -- Juvenile literature; Ecology -- Juvenile literature